EFFECTS OF MALARIA PARASITEMIA ON HAEMATOLOGICAL PARAMETERS OF PREGNANT WOMEN ATTENDING GOMBE SPECIALIST HOSPITAL - F. A, YUSUF; Y, SADAU; P. A, NATASHA; I, LAI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Malaria is a major public health problem in Sub-Saharan Africa. Most of the infections are asymptomatic, affecting mainly pregnant women and children. Blood samples were collected from 384 pregnant women. Data analysis was done using statistical package for social science version 20.0. Bivariate and Multivariate analysis were performed hence the P - value of less than 0.05 was considered significant. Out of the 284 (74%) pregnant women infected with malaria, 40.8% were within the age (21-25). Which has the highest rate of infection, whereas the lowest was ≥ 31 years (9.9%). The rate of infection base at the gestational age of pregnant women in the study tells that first trimester had the highest rate (41.9%) and third trimester had the lowest rate of infection (20.1%). In some of the hematological parameters, the total WBC, absolute lymphocytes and monocytes were significantly higher in the malaria infected patients than in non-infected pregnant women (P < 0.05). There was no significant difference in the basophil count between the malaria positive and the controls (P > 0.05). There was a significant difference in the levels of WBC, PLTC and MCV, MCH and MCHC; the insignificant difference between the first, second and third trimester of the positive cases and negative. In conclusion, Malaria infection can increase some of the physiological changes associated with pregnancy and should be prevented to save lives of the mothers and the babies.